Pengembangan Multimedia Interaktif dalam Pembelajaran Bangun Datar Matematika Kelas IV SDN 3 Karangasem Grobogan - Hermawan, Hendrik, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr. Sumardi, M.Si (2016)
The purpose of this study is: 1) describe characteristics of instructional media in teaching Math Class IV are valid, practical, and effective. 2) Describe the characteristics of learning using interactive learning media development results. This type of research is development research with descriptive method, experimentation and evaluation. The subjects were students and teachers in Class IV SDN 3 Karangasem and SDN 2 Wirosari. Data were collected using a sheet of validity, observation, questionnaires and tests. The results showed: 1) Characteristics of interactive learning media in learning mathematics class IV are valid, practical, and effective: a) include SK, KD and objectives, b) there is consistency subject matter with the purpose, c) combining text, narration, and images and animation, d) gives students opportunity to conduct exploratory activities, e) provide exercises are equipped with feedback. 2) Characteristics of learning using interactive learning media development results are: a) begins with explanation of objectives, b) each indicator is described media interactive learning through pictures, narration, and animation, c) deepening every indicator is done by providing application simulatif at each end of discussion, d) exercises given media interactive learning to train students to solve a mathematical problem, e) interactive learning media can be used to measure the level of student understanding.